METODE QUANTUM LEARNING DALAM MENINGKATKAN SELF AWARENESS DAN MOTIVASI SADARI PADA REMAJA - Dhina Widayati; Farida Hayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
Breast cancer is at risk at all ages including teenagers as well. However, adolescents are not yet aware of the need for early detection of breast cancer, so it requires mehods to increase awareness of importance of early detection measures. The purpose of this research is to know the influence of Quantum learning methods on Self awareness and the motivation to check breasts themselves on class XI students in MA Al Fatah Badas. The design of this research is Pre experimental design with One Group pretest-posttest Design. research plan. The population of all XI class students in MA Al Fatah Badas, sample 27 respondents, taken with a total sampling technique. Analyze pre and post interventions on self awareness and motivation variables. This research variable data was tested with the Wilcoxon statistical test with a -value signification of 0.00 (α = 0.05). The results of the self Awareness variable study showed the rate of self awareness of respondents prior to almost all interventions (88.89%) with low categories and after almost all interventions (92.59%) with good category. While the results of the motivation variable study showed the motivation level of respondents before the intervention almost all (88.89%) with the low category and after total intervention (100%) with high category. There is an influence on the quantum learning method of self awareness and the motivation to examine the breasts themselves with the value of -value self awareness of 0.00 (α = 0.05) while the value of the -value motivation is 0.00 (α = 0.05). The quantum learning method is a fun and interesting learning model so that the material can be well absorbed. This learning method invites students to participate actively in learning activities so as to allow them to explore their curiosity. Based on this research, learners are advised to use quantum learning methods to increase interest in classroom learning.